The ribosome and its role in protein folding: looking through a magnifying glass. Issue 6 (5th June 2017) - Javed, Abid; Christodoulou, John; Cabrita, Lisa D.; Orlova, Elena V.
Abstract : The structural biology of co‐translational protein folding on the ribosome is reviewed. Abstract : Protein folding, a process that underpins cellular activity, begins co‐translationally on the ribosome. During translation, a newly synthesized polypeptide chain enters the ribosomal exit tunnel and actively interacts with the ribosome elements – the r‐proteins and rRNA that line the tunnel – prior to emerging into the cellular milieu. While understanding of the structure and function of the ribosome has advanced significantly, little is known about the process of folding of the emerging nascent chain (NC). Advances in cryo‐electron microscopy are enabling visualization of NCs within the exit tunnel, allowing early glimpses of the interplay between the NC and the ribosome. Once it has emerged from the exit tunnel into the cytosol, the NC (still attached to its parent ribosome) can acquire a range of conformations, which can be characterized by NMR spectroscopy. Using experimental restraints within molecular‐dynamics simulations, the ensemble of NC structures can be described. In order to delineate the process of co‐translational protein folding, a hybrid structural biology approach is foreseeable, potentially offering a complete atomic description of protein folding as it occurs on the ribosome.